Kepemimpinan kepala sekolah dalam menjaga tata kelola sekolah selama masa pandemi Covid-19 - Bernadetha Nadeak; Citra Puspa Juwita (Jurnal Konseling dan Pendidikan, 2020)
This study aims to analyze the leadership of school principals in learning during the Covid-19 pandemic. This study used a quantitative descriptive research method with as many as 63 school principals as respondents who were scattered throughout Indonesia. Data collection was carried out online using an open questionnaire via the google form platform. The data were then analyzed using theme and percentage analysis to measure and analyze the conditions of learning governance during the Covid-19 pandemic. The results showed that 54.55% of the learning activities in schools were carried out online during the Covid-19 pandemic. Then in online learning activities 36.89% use google classroom, 20.39% use zoom, and 15.53% use Whatsapp. Most of the applications used to carry out online learning activities are Google classroom, Zoom and WhatsApp and a few others use other applications. Some of the governance processes in schools have been carried out well but some have not been maximized because they are constrained by the availability of facilities, networks, tools and the limited skills of teachers in using technological media. Learning strategies as well as discussions and strengthening between school principals and school personnel are needed to maximize school governance especially during the Covid-19 pandemic.